2023
DOI: 10.1039/d2tb02202h
|View full text |Cite
|
Sign up to set email alerts
|

A nitric oxide responsive AIE probe for detecting the progression of osteoarthritis

Abstract: An AIE probe was established for reacting with NO and emitting fluorescence in arthritic joints/chondrocytes. This AIE probe is appropriate for detecting the progression of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It was derived from tetraphenylethylene (TPE) modified with a hydrophilic-group polyethylene glycol chain and anti-inflammatory drug diacerein to improve water solubility and poor fluorescence. 40,41 The o-phenylenediamine group was selec- Reproduced with permission. 38 Copyright 2019, Royal Society of Chemistry.…”
Section: No Probes Associated With Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…It was derived from tetraphenylethylene (TPE) modified with a hydrophilic-group polyethylene glycol chain and anti-inflammatory drug diacerein to improve water solubility and poor fluorescence. 40,41 The o-phenylenediamine group was selec- Reproduced with permission. 38 Copyright 2019, Royal Society of Chemistry.…”
Section: No Probes Associated With Cancermentioning
confidence: 99%
“…It was derived from tetraphenylethylene (TPE) modified with a hydrophilic-group polyethylene glycol chain and anti-inflammatory drug diacerein to improve water solubility and poor fluorescence. 40,41 The o -phenylenediamine group was selectively reacted with NO to form a benzotriazole group and produce a strong red fluorescence signal. The results showed that the NO-responsive AIE probe can monitor the progression of OA in vivo and in vitro during with fluorescence response change.…”
Section: No Probes Associated With Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of aggregation-induced emission (AIE), as proposed by Tang's group, 20 refers to some luminescent molecules such as benzothiazole, 21,22 tetraphenylethene, [23][24][25][26] and triphenylamine [27][28][29] that could display intense fluorescent emission behavior in the aggregated state due to the restriction of intramolecular motions (RIM). On the other hand, excitedstate intramolecular proton transfer (ESIPT), first reported by Weller in the 1995, involves emission by fast intramolecular proton transfer via the extremely fast enol-keto tautomeric transformation between the ground state and excited state upon photoexcitation with the advantages of good photostability and large Stokes shifts, thereby avoiding the adverse effect of self-absorption and inner-filter.…”
Section: Introductionmentioning
confidence: 99%